Safety of breast feeding during rituximab treatment in multiple sclerosis. Issue 1 (25th July 2022) - Rød, Brit Ellen; Torkildsen, Øivind; Myhr, Kjell-Morten; Bø, Lars; Wergeland, Stig
Abstract : Background: There are limited data on the safety of breast feeding during rituximab therapy. Our objective is to determine exposure from breast feeding and biological effects of rituximab in breastfed infants. Methods: In our case series of six mother–infant pairs, the nursing mothers with relapsing-remitting multiple sclerosis received rituximab during breast feeding. As part of clinical follow-up, six serial breast milk samples, and blood samples from both mothers and infants, were collected and analysed. Results: The median average rituximab concentration (Cavg ) in breast milk was 0.04 µg/mL and the estimated relative infant dose (RID) was 0.07%. The highest measured concentration of rituximab in the breast milk samples was 0.25 µg/mL, giving an estimated RID of 0.26%. All infant serum rituximab concentrations were below 0.01 µg/mL. The CD19 +B cell count values were within the 10th– 90th percentiles of reported normal ranges in healthy infants. Conclusions: We found minimal transfer of rituximab into breast milk and could not reliably detect levels of rituximab in infant serum. B cell counts in infants were unaffected.